(untitled) (Foro de Educacion, 2024)
Maria Montessori was one of the most important female figures in the 20th-century Italian pedagogical overview. She deeply examined the child and his/her “absorbing” mind in a way that clarified the significant role played by the environment in cognitive and emotional education. Il metodo della pedagogia scientifica (1909) was her first study where she pointed out that science should analyse how the child’s personality develops in social interaction. Maria Montessori claimed children’s rights with respect to the adults’ world by underlining the traditional error -in psychological and educational terms-which used to compel the child to act not complying with his/her own nature. To this end, she organized the child’s educational context-that is the kindergarten- like an ideal place where the child could live his/her educational experiences by freely acting and by being appropriately stimulated. Montessori’s thought has led to fruitful implications related to such pedagogical topics as those currently tackled in contemporary pedagogy: i.e.: the relation between environment and education, the organization of the teaching and learning process, the use of procedures, methodologies and materials designed for a relevant pedagogical intervention.